The prevalence of chronic conditions in patients diagnosed with one of 29 common and rarer cancers: A cross-sectional study using primary care data. (December 2020) - Koo, Minjoung Monica; Swann, Ruth; McPhail, Sean; Abel, Gary A.; Renzi, Cristina; Rubin, Greg P.; Lyratzopoulos, Georgios
Highlights: Most patients had at least one morbidity; nearly one in two had multiple morbidities. Morbidity prevalence was similar across cancers but with notable exceptions. Related enquiries should take account of certain combinations of morbidities and cancer. Abstract: Background: Pre-existing chronic conditions (morbidities) influence the diagnosis and management of cancer. The prevalence of specific morbidities in patients diagnosed with common and rarer cancers is inadequately described. Methods: Using data from the English National Cancer Diagnosis Audit 2014, we studied 11 pre-existing morbidities recorded as yes/no items by participating general practitioners based on information included in primary care records. We examined the number and type of morbidities across socio-demographic and cancer site strata, and subsequently estimated observed and age/sex standardised prevalence of each morbidity by cancer. Results: Over three-quarters (77 %; 11, 429/14, 774) of non-screen-detected patients had at least one chronic condition before diagnosis, while nearly half (47 %) had two or more. Hypertension (39 %) and physical disability (2%) were the most and least common conditions. Male, older and more socio-economically deprived patients were more likely to have at least one morbidity (p < 0.001 for all between variable group comparisons). For most morbidities, the standardised prevalence was similar across different cancers with a few exceptions, including respiratory disease prevalence being greatest among lung cancer patients and diabetes prevalence being greatest among liver, pancreatic, and endometrial cancer patients. Conclusions: Most cancer patients have at least one morbidity, while almost one in two have two or more. The findings highlight the need to take certain morbidity- and cancer-site combinations into account when examining associations between morbidity and cancer outcomes.